Kerangka Hukum Harmonisasi Peraturan Daerah Dalam Perspektif Teori Hirarki Perundang-Undangan - Ikhwan, Yeni Nel; Khairani, Khairani (Nagari Law Review, 2023)
In Indonesia, it is known that there is a hierarchy of statutory regulations, known as the hierarchy of statutory regulations, which is based on the provisions of Article 7 paragraph (1) of Undang-Undang Nomor 12 Tahun 2011. This hierarchy of laws and regulations has the consequence of the provision that lower laws and regulations must not conflict with higher laws and regulations. Regional regulations as part of statutory regulations are also subject to this hierarchical concept. To guarantee the concept of hierarchy, it was then determined that there would be harmonization of regional regulations which were standardized in Undang-Undang Nomor 12 Tahun 2011, which was last amended by Undang-Undang Nomor 13 Tahun 2022. However, the provisions for the harmonization process contained in the Law were not accompanied by the establishment of implementing regulations that discussed in detail the procedures and methods for harmonization. This article will discuss further the position of the harmonization process for regional regulations in theory and how the process of harmonizing regional regulations is implemented in practice in Indonesia. So it is hoped that in the future recommendations will be able to be formulated for the process of harmonizing regional regulations which will make a positive contribution to efforts to overcome overregulation in the region.